A Retrospective Analysis of Clinical Characteristics and Neutrophil-to-Lymphocyte Ratio in Hospitalized Indonesian Patients with Pemphigus Vulgaris and Bullous Pemphigoid: A Single-Center Experience - Azhar Arrosyid; Nurrachmat Mulianto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Comprehensive clinical-epidemiological data on severe autoimmune bullous diseases (ABDs) from Southeast Asian populations are notably scarce. Pemphigus vulgaris (PV) and bullous pemphigoid (BP) are the most common ABDs, and understanding their presentation in diverse ethnic and geographic contexts is crucial for global health equity. This study’s primary aim was to characterize a cohort of hospitalized ABD patients in Central Java, Indonesia, and to secondarily explore the behavior of the neutrophil-to-lymphocyte ratio (NLR) as an inflammatory marker within this real-world clinical setting. Methods: A retrospective, cross-sectional study was conducted at a tertiary referral hospital in Surakarta, Indonesia. The study included all patients admitted with a final diagnosis of PV or BP between January 2019 and December 2023. Comprehensive data on demographics, documented comorbidities, duration of hospitalization, and admission hematological parameters were extracted from medical records. Clinical characteristics were compared, and the non-parametric Mann-Whitney U test was used to analyze the difference in NLR. A post-hoc power analysis was performed to contextualize the hematological findings. Results: This study provides a detailed clinical profile of 30 hospitalized ABD patients. The PV cohort (n=17) was characterized by a younger age of onset (mean age 54.29 ± 14.83 years) and a strong female predominance (70.6%). In contrast, the BP cohort (n=13) was older (mean age 63.08 ± 22.01 years) with a balanced gender distribution. A key finding was that patients with PV had a significantly longer duration of hospitalization than those with BP (13.24 vs. 10.15 days, p < 0.05). The mean NLR was descriptively higher in BP (10.56 ± 7.22) than in PV (9.43 ± 6.14), but this difference was not statistically significant (p = 0.770), a finding consistent with the study’s critically low statistical power of 9.8%. Conclusion: This study presents a valuable clinical and epidemiological snapshot of hospitalized patients with PV and BP in an underrepresented Indonesian population, highlighting a significantly greater clinical burden for PV as quantified by length of stay. The exploratory analysis of the NLR was inconclusive and should not be interpreted as definitive evidence against its utility. Instead, it serves as a powerful illustration of how the effects of low statistical power and overwhelming, unmeasured confounding from disease severity and corticosteroid treatment present profound challenges to the validation of non-specific biomarkers in complex, real-world clinical scenarios.